2020
DOI: 10.15282/mohe.v9i2.428
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Compression Socks on Postural Balance Among University Netball Players

Abstract: The purpose of this study was to observe the effects of wearing compression socks on postural balance in university netball players. Fourteen advanced learners' netball players performed three trials (20 seconds for each trial) of dynamic postural balance test on Biodex Stability System, in two socks conditions, (a) Normal Socks and (b) Compression Socks.  Data on overall, anterior/posterior and medial/lateral stability indexes were analyzed using Paired Sample T-tests. Results revealed that wearing compressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Maintaining the integrity of the ankle joint is crucial for postural stability. Ankle instability could result in altered biomechanics throughout the body, making ankle stability highly correlated to the risk of injury and putting those with poor balance at greater risk of injury [9]. Lephart et al (1998) revealed decreased sensory feedback in those with ligamentous injuries, which shows the importance of stimulation of neurological feedback mechanisms in the musculotendinous and articular structures to maintain postural stability [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Maintaining the integrity of the ankle joint is crucial for postural stability. Ankle instability could result in altered biomechanics throughout the body, making ankle stability highly correlated to the risk of injury and putting those with poor balance at greater risk of injury [9]. Lephart et al (1998) revealed decreased sensory feedback in those with ligamentous injuries, which shows the importance of stimulation of neurological feedback mechanisms in the musculotendinous and articular structures to maintain postural stability [10].…”
Section: Discussionmentioning
confidence: 99%
“…The body is a closed kinetic chain; therefore, ankle instability could result in altered biomechanics throughout the body, increasing the risk of injury, especially for individuals with poor balance [9]. Similarly to the effects of aging on sensory information and motor outputs, a decrease in sensory feedback is observed in individuals with ligamentous injuries, which reveals that neurological feedback mechanisms originating from the articular and musculotendinous structures are crucial for the maintenance of joint stability [9,10]. This further supported Freeman (1965), who explained that alteration in postural control could be due to the deficits in afferent input from mechanorecpetors in ankle ligaments [11].…”
Section: Introductionmentioning
confidence: 99%